2016
DOI: 10.18805/asd.v0iof.9624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic manures on growth and yield of summer cowpea [Vigna unguiculata (L.) Walp] under middle Gujarat conditions

Abstract: An experiment was carried out on loamy sand soil of Bidi tobacco Research Station Farm, AAU, Anand to evaluate the effect of organic manures (farmyard manure, vermi-compost, poultry manure, neem cake and castor cake) on growth and green pod yield of cowpea during summer season of 2013-14 in randomized block design with four replication. Application of recommended dose of fertilizer 20-40-0 NPK kg ha -1 recorded significantly higher green pod, stover yield and yield contributing characters viz., number of green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
8
10
0
Order By: Relevance
“…The above findings are in confirmation with the research findings of Shrikant (2010) and Erdal et al, 2008. Vermicompost treatments greater root extension under biofertilizers application might have helped in greater uptake of nutrients which ultimately improved the yield attributing characters like pod length, pod yield, pod weight, number of pods per plant and number of seeds per pod (Joshi et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…The above findings are in confirmation with the research findings of Shrikant (2010) and Erdal et al, 2008. Vermicompost treatments greater root extension under biofertilizers application might have helped in greater uptake of nutrients which ultimately improved the yield attributing characters like pod length, pod yield, pod weight, number of pods per plant and number of seeds per pod (Joshi et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…Increased weight of root nodule in organic mulch treatment might be due to favourable effect of paddy straw organic mulch in improving the overall physical, chemical and biological attributes of the soil and thus improving root symbiosis process with soil nodule rhizobacteria thereby enhancing root nodulation activity of Rhizobium in the soil. Similar results were reported by Goud et al, (2010) and Joshi et al, 2016. On the basis of the results obtained from the current study, it is clear that use of various organic and plastic/inorganic mulches has profound effects on root development and root nodulation in cowpea plants, however, application of different irrigation level has resulted in the variable type of findings. Among various treatments of organic and plastic mulches, organic mulches application has positive effects on most of the parameters associated with root development and nodulation, while it was negatively affected by black mulches.…”
Section: Fresh Weight Of Total Nodule Plantsupporting
confidence: 92%
“…Overall findings showed that in studied area modern agriculture based on only chemicals fertilizer will not be prosperous because of many problems such as poor soil condition, imbalanced nutrients, surface and ground water pollution from fertilizers and sediments impending shortages of non-renewable resources and low farm income from high production costs (Joshi et al, 2016). However, there is increasing awareness of the need for corrections in nutritional management in chickpea production system in semi-arid region.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, in normal soils with some organic matter content, exchangeable cations such as Ca 2+ and Mg 2+ link clay particles to humic acids of the organic matter, generating stable micro-aggregates which are the basis for soil structure, porosity, and internal drainage (Machado and Serralheiro, 2017). Furthermore, modern agriculture based on merely chemicals is not sustainable because of many problems such as loss of soil productivity from excessive erosion and associated plant nutrient losses, surface and ground water pollution from pesticides, fertilizers and sediments impending shortages of non-renewable resources and low farm income from high production costs (Joshi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%